2020 International Conference on UK-China Emerging Technologies (UCET) 2020
DOI: 10.1109/ucet51115.2020.9205373
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning to Predict the Future Development of Disease

Abstract: The objective of this research is to develop a longterm risk model for the development of cardiovascular disease (CVD) because of type-2 diabetes (T2D). We use the support vector machine (SVM) and the K-nearest neighbours algorithms on the dataset collected from a longitudinal study called Framingham Heart Study, to develop the prediction models. The dataset was first balanced by the Synthetic Minority Oversampling Technique algorithm. The SVM algorithm was then used to train the model, and after tuning the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 16 publications
(17 reference statements)
0
5
1
Order By: Relevance
“…While the ensemble algorithms used in this study (XGBoost and AdaBoost) outperformed the Naive Bayes algorithm, it's important to note that their performance differences were not significant. Furthermore, the best-performing model in this study fell significantly short in terms of accuracy when compared to the study conducted by Miao et al [7]. Specifically, our study achieved an accuracy rate of 71%, whereas Miao et al reported a much higher accuracy of 96.9%.…”
Section: B Models Developmentcontrasting
confidence: 86%
See 1 more Smart Citation
“…While the ensemble algorithms used in this study (XGBoost and AdaBoost) outperformed the Naive Bayes algorithm, it's important to note that their performance differences were not significant. Furthermore, the best-performing model in this study fell significantly short in terms of accuracy when compared to the study conducted by Miao et al [7]. Specifically, our study achieved an accuracy rate of 71%, whereas Miao et al reported a much higher accuracy of 96.9%.…”
Section: B Models Developmentcontrasting
confidence: 86%
“…Another study was conducted by Miao et al [7]. In their research, they utilized the Framingham Heart Study dataset along with Support Vector Machine (SVM) and k-Nearest Neighbors (KNN) algorithms to predict cardiovascular disease in T2DM patients.…”
Section: Related Workmentioning
confidence: 99%
“…The concept of prediction using longitudinal data is of great importance in the medical field. There are works in the literature that exploit ML and DL for prediction tasks even outside the field of HF [27,28].…”
Section: Related Workmentioning
confidence: 99%
“…Model forecasts without the costly and cumbersome examination of oral glucose tolerance. Following testing on the Framingham Heart Study dataset, the model yielded high-performance outcomes [5].…”
Section: Related Workmentioning
confidence: 99%